2013
DOI: 10.4097/kjae.2013.65.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warmed inspired gases on body temperature during arthroscopic shoulder surgery under general anesthesia

Abstract: BackgroundPerioperative hypothermia can develop easily during shoulder arthroscopy, because cold irrigation can directly influence core body temperature. The authors investigated whether active warming and humidification of inspired gases reduces falls in core body temperature and allows redistribution of body heat in patients undergoing arthroscopic shoulder surgery under general anesthesia.MethodsPatients scheduled for arthroscopic shoulder surgery were randomly assigned to receive either room temperature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Third, a forced-air warming device should have been applied to patients whenever body temperatures fell below 36.5℃ during the operation and below 36℃ in the PACU according to the National Institute for Health and Care Excellence (NICE) clinical guideline 65. This study adopted a lower temperature than that suggested in the NICE guideline before active warming measures, referring to other studies [ 2 3 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, a forced-air warming device should have been applied to patients whenever body temperatures fell below 36.5℃ during the operation and below 36℃ in the PACU according to the National Institute for Health and Care Excellence (NICE) clinical guideline 65. This study adopted a lower temperature than that suggested in the NICE guideline before active warming measures, referring to other studies [ 2 3 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of hypothermia less than 36.0℃ in patients undergoing arthroscopic surgery under general anesthesia, especially when large amounts of cold fluid are used despite short operating times [ 2 , 8 , 21 ]. It has been reported that during arthroscopic hip surgery, body temperature tends to decline and the incidence of hypothermia below 35.0℃ was 2.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Jo et al [ 8 ] reported that core temperatures were significantly higher from 75 minutes to 120 minutes after anesthetic induction with HHC use in arthroscopic shoulder surgery than in a group using an unheated conventional respiratory circuit, but there was no significant difference in hypothermia below 36.0℃ between the two groups. There was a significant difference in core temperature reduction between the two groups, as was found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations